Hospitalization stress and coping in children - Lebre Dias, Tatiane; Ribeiro de Moraes, Alessandra; Marques Brito, Thiago; Brunoro Motta, Alessandra; Fiorim Enumo, Sônia Regina (O Mundo da Saúde, 2023)
Hospitalization is stressful for children and their families that can affect health outcomes, depending on how they face the situation. This study analyzed how children deal with indicators of physiological and psychological stress related to hospitalization. Participants were 20 children aged five years old, most of them hospitalized for chronic diseases, in a public hospital in Cuiabá, MT. The following were applied individually in the playroom library: a) Morning and late afternoon salivary cortisol index to measure physiological stress; b) Interview script on illness and hospitalization - child version; and c) Hospitalization Coping Scale (COPE-H). Salivary cortisol was above that indicated in four children. More than half of the sample reported having difficulties caused by the disease to perform several activities; invasive medical procedures are more aversive. They also presented psychological stress responses, with coping of involuntary and voluntary disengagement within the mean age. They reported adaptive strategies to deal with hospitalization, such as watching TV, talking, taking medication and, especially, playing, evaluated as a stress reducer by almost half of the children. However, half of the sample presented a poorly adaptive coping pattern of hospitalization below that expected for their age. There were no significant correlations between salivary cortisol index and coping. Consistent with the literature of the area on the limitations imposed by hospitalization and psychosocial consequences for the child and the caregiving family, the results indicate the importance of interventions in the coping of hospitalization for this population in this age group.